Different Heart Rate Patterns During Cardio-Pulmonary Exercise (CPX) Testing in Individuals With Type 1 Diabetes - Moser, Othmar; Tschakert, Gerhard; Mueller, Alexander; Groeschl, Werner; Eckstein, Max L.; Koehler, Gerd; Bracken, Richard M.; Pieber, Thomas R.; Hofmann, Peter (Frontiers in Endocrinology, 2018)
To investigate the heart rate during cardio-pulmonary exercise (CPX) testing in individuals with type 1 diabetes (T1D) compared to healthy (CON) individuals. Fourteen people (seven individuals with T1D and seven CON individuals) performed a CPX test until volitional exhaustion to determine the first and second lactate turn points (LTP1 and LTP2), ventilatory thresholds (VT1 and VT2) and the heart rate turn point. For these thresholds cardio-respiratory variables and percentages of maximum heart rate, heart rate reserve, maximum oxygen uptake and oxygen uptake reserve and maximum power output were compared between groups. Additionally, the degree and direction of the deflection of the heart rate to performance curve (kHR) were compared between groups. Individuals with T1D had similar heart rate at LTP1 (mean difference) -11, ((95% confidence interval) -27 to 4 b.min-1), at VT1 (-12, -8 to 33 b.min-1) and at LTP2 (-7, -13 to 26 b.min-1), at VT2 (-7, -13 to 28 b.min-1) and at the heart rate turn point (-5, -14 to 24 b.min-1) (p = 0.22). Heart rate expressed as percentage of maximum heart rate at LTP1, VT1, LTP2, VT2 and the heart rate turn point as well as expressed as percentages of heart rate reserve at LTP2, VT2 and the heart rate turn point was lower in individuals with T1D (p<0.05). kHR was lower in T1D compared to CON individuals (0.11 ± 0.25 vs. 0.51 ± 0.32, p = 0.02). Our findings demonstrate that there are clear differences in the heart rate response during CPX testing in individuals with T1D compared to CON individuals. We suggest using submaximal markers to prescribe exercise intensity in people with T1D, as the heart rate at thresholds is influenced by kHR.